Perbedaan Tingkat Dehidrasi Dan Kelelahan Pada Pekerja Terpapar Iklim Kerja Panas Di Bagian Pengepakan Dan Pelintingan Di PT. Panen Boyolali - Tasyrifah, Ghina Mutiara; , Tarwaka, PGDip.Sc., M.Erg (2017)
When worker is doing a job, there are many dangerous factor around work place. One of those is psychic factor on work place such as work climate. Extreme heat pressure can cause increased discharge of body fluids through sweat, and then make dehydration and other problem health such as fatigue. The aim of this research is to know the difference level of dehydration and fatigue on exposure labor by hot working climate. Method of this research is analytic observational by using cross sectional approach. The technique of sampling is simple random sampling with the amount of sample are 100 respondents with 160 labors population. The analysis data uses independent sample t-test with sig level α = 0,05. The result of research shows that there is significant difference between level of dehydration and fatigue on packing section higher than rolling section with score (p = 0,004) and (0,000). It can be concluded that work climate at packing influence the occurrence of dehydration and fatigue on labor. It is recommended on company to pay attention work climate on work environment and for labor, suggested to consume mineral water, minimum 8 glasses or 2 liters per day, and take time to have a rest in order to avoid from dehydration and fatigue.